2020
DOI: 10.1177/1533033820973276
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-185 Is a Diagnostic and Prognostic Biomarker for Non-Small Cell Lung Cancer

Abstract: Objective: MicroRNAs (miRNAs) have been found to play important roles in the development of non-small cell lung carcinoma (NSCLC). The aim of this study was to analyze the expression and clinical value of serum miR-185 in NSCLC. Methods: Serum miR-185 levels were detected in 146 NSCLC patients, 50 patients with carcinoma in situ, 25 patients with non-malignant lung diseases (NMLD), and 80 healthy controls using quantitative reverse transcription PCR. The correlation between serum miR-185 level and clinical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…158 Others reported an association between miR-153, 159 miR-494, 160 miR-519d 161 and more advanced clinical stage, presence of lymph node metastases, and worse OS in NSCLC patients. Similar results regarding a poor prognosis in NSCLC patients were reported for the downregulation of miR-184, 162 miR-185, 163 miR-770, 164 and miR-30a-5p, 165 , and the upregulation of miR-23b-3p, miR-10b-5p and miR-21-5p, 166 miR-31, 167 miR-378, 168 miR-942, and miR-601. 169 On the contrary, a high expression of miR-3195 resulted in longer OS, 170 while miR-21 and miR-4257 were established as predictors of NSCLC recurrence.…”
Section: Microrna As a Lung Cancer Markersupporting
confidence: 85%
“…158 Others reported an association between miR-153, 159 miR-494, 160 miR-519d 161 and more advanced clinical stage, presence of lymph node metastases, and worse OS in NSCLC patients. Similar results regarding a poor prognosis in NSCLC patients were reported for the downregulation of miR-184, 162 miR-185, 163 miR-770, 164 and miR-30a-5p, 165 , and the upregulation of miR-23b-3p, miR-10b-5p and miR-21-5p, 166 miR-31, 167 miR-378, 168 miR-942, and miR-601. 169 On the contrary, a high expression of miR-3195 resulted in longer OS, 170 while miR-21 and miR-4257 were established as predictors of NSCLC recurrence.…”
Section: Microrna As a Lung Cancer Markersupporting
confidence: 85%
“…A study by Sun et al has shown that serum miR30a-5p may function as a new biomarker for the diagnosis and prognosis of colorectal cancer [ 26 ]. Serum miR-185 [ 27 ] and serum miR1246 [ 28 ] have been found to be used as diagnostic and prognostic biomarkers for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The role of miR-185 in oral cancer (131), prostate cancer (132) and in NSCLC has been previously evaluated (133,134). In 2020, Liu et al (68) demonstrated that serum miR-185 might be a promising biomarker for NSCLC early detection. Their work showed significantly reduced miR-185 expression in NSCLC patients with lymph node metastasis at the advanced stage or with poor differentiation.…”
Section: Circulating Mirnas As Diagnostic Biomarkers For Nsclcmentioning
confidence: 99%
“…Significantly, miR-518b over-expression was likewise associated with shorter survival of patients (p = 0.009). J. Liu et al (68) as first demonstrated that decreased level of serum miR-185 was markedly associated with worse survival and adverse clinicopathological parameters in NSCLC patients. Performing univariate and multivariate Cox regression analysis indicated that this miRNA was an independent prognostic indicator for NSCLC.…”
Section: Circulating Mirnas As Diagnostic Biomarkers For Nsclcmentioning
confidence: 99%